2018
DOI: 10.5539/jas.v10n2p15
|View full text |Cite
|
Sign up to set email alerts
|

Sugarcane Crop Residue and Bagasse Allelopathic Impact on Oat (Avena sative L.), Tall Morningglory (Ipomoea purpurea L. Roth), and Redroot Pigweed (Amaranthus retroflexus L.) Germination

Abstract: Allelopathy, the chemical interaction between plants, may result in the inhibition of plant growth and development, and includes compounds released from a primary crop that adversely impact crop or weed species. The objective of this research was to observe the allelopathic impact of sugarcane (Saccharum sp.) post-harvest crop residue and mill bagasse leachate on seed germination of three other plant species. Oat (Avena sative L.) var. 'Corral', tall morningglory (Ipomoea purpurea L. Roth), and redroot pigweed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 33 publications
0
1
0
Order By: Relevance
“…The leachates from PHR have been shown to negatively affect weed seed germination and plant development (Viator et al 2006). Weed seeds sensitive to 100 g L −1 of postharvest sugarcane residue leachates included red morningglory (Ipomoea coccinea L.), tall morningglory [Ipomoea purpurea (L.) Roth], redroot pigweed (Amaranthus retroflexus L.), and spiny amaranth (Amaranthus spinosus L.) (Viator et al 2006;Webber et al 2017Webber et al , 2018. Although studies have shown the benefits of PHR reducing weed emergence, other research indicates that the mulching activity of the residue can reduce subsequent sugarcane yields (Judice et al 2007;Viator et al 2005;Viator and Wang 2011).…”
Section: Introductionmentioning
confidence: 99%
“…The leachates from PHR have been shown to negatively affect weed seed germination and plant development (Viator et al 2006). Weed seeds sensitive to 100 g L −1 of postharvest sugarcane residue leachates included red morningglory (Ipomoea coccinea L.), tall morningglory [Ipomoea purpurea (L.) Roth], redroot pigweed (Amaranthus retroflexus L.), and spiny amaranth (Amaranthus spinosus L.) (Viator et al 2006;Webber et al 2017Webber et al , 2018. Although studies have shown the benefits of PHR reducing weed emergence, other research indicates that the mulching activity of the residue can reduce subsequent sugarcane yields (Judice et al 2007;Viator et al 2005;Viator and Wang 2011).…”
Section: Introductionmentioning
confidence: 99%